Knowledge, Attitude, Practice And Stigma Of Tuberculosis Among Healthcare Providers In Hospital Sultan Haji Ahmad Shah, Temerloh, Pahang - Nuralia Akma; Mohamad Mustafa; Siti Aishah Suran; Abdul Aziz Marwan; Mohd Rahman Omar (Pharmascope Publications, 2024)
Malaysia is categorized as an intermediate tuberculosis (TB) burden country by World Health Organisation. This cause great challenge as an occupational hazard for healthcare providers (HCPs) in Malaysia, as they received two- to three-fold greater risk of contracting TB than the general population. This cross-sectional questionnaire study aimed to assess HCPs' knowledge, attitude, practice, and stigma (KAPS) towards TB in Hospital Sultan Haji Ahmad Shah, Temerloh. A pilot-tested questionnaire was designed based on the WHO recommendation for KAPS study in TB. A survey was carried out between September 2018 and February 2019. Data were analyzed using SPSS version 25.The majority of respondents have moderate knowledge (75%) and practice (93%) on tuberculosis whilst scored lower on attitude (49%). Average self-perceived stigma was observed (67%) with higher sympathy (73%). Overall knowledge and practice on tuberculosis among HCPs in HOSHAS was good with some misconceptions about disease transmission. However, more works needed to improve the attitude and stigma towards TB, as it may affect health services delivery towards TB patients.